Differential expression profiles of oxidative stress levels, 8-oxo-dG and 4-HNE, in Barrett?s esophagus compared to esophageal adenocarcinoma - Phelan, James; Reynolds, John; Ravi, Narayanasamy (My University, 2019)
Barrett’s esophagus (BE), a chronic inflammatory condition, is the leading risk factor for esophageal adenocarcinoma (EAC). In inflammation to cancer pathways, oxidative stress profiles have been linked to cancer progression. However, the relevance of oxidative stress profiles along the BE-disease sequence remains to be elucidated. In this study, markers of oxidative stress; DNA adducts (8-oxo-dG) and lipoperoxidation (4-HNE), and markers of proliferation (Ki67) were measured in patient biopsies representing the BE-disease sequence. Differences in expression of these markers in Barrett’s patients with cancer-progression and non-progression were examined. Proliferation was reduced in Barrett’s specialized intestinal metaplasia (SIM) compared with EAC (p < 0.035). Correcting for cell proliferation levels, a confounding factor, linked to oxidative stress profiles, SIM demonstrated increased levels of 8-oxo-dG and 4-HNE (p < 0.05) compared with EAC. Longitudinal analysis of Barrett’s patients demonstrated decreased levels of 8-oxo-dG in SIM cancer progression (p < 0.05). BE is an environment of increased oxidative stress and inflammation. Patients with progressive disease demonstrated reduced oxidative stress levels in 8-oxo-dG. Perhaps these alterations facilitate Barrett’s progression, whereas in non-progressive disease, cells follow the rules of increased oxidative stress ultimately triggers cell apoptosis, thereby preventing propagation and survival.
PUBLISHED
Keywords: Mitochondrial instability; Oxidative stress; Barrett's esophagus; Esophageal Adenocarcinoma; Cancer